Menggerakan Wakaf Kompos; Aksi Lokal Penguatan Peran Ekologis Masjid untuk Mitigasi Perubahan Iklim - Suhendi; Umar; Zusy Aryanti; Siti Annisah; Ahmad Syaferi (CV. Creative Tugu Pena, 2024)
The objective of this community service project is to explore and strengthen the role of mosques as ecological agents in mitigating climate change through the innovative “Compost Waqf” initiative. Conducted at Nurul Amin Mosque in Metro City, this study employed a Community-Based Research (CBR) and Participatory Rural Appraisal (PRA) approach, involving 120 participants, including mosque administrators and congregants. This program integrates Islamic teachings with practical solutions for managing organic waste, enhancing environmental literacy, and fostering climate action awareness among mosque attendees. By focusing on waste segregation and composting, the initiative significantly reduced organic waste, minimized greenhouse gas emissions, and provided sustainable economic benefits for mosque operations and community empowerment. This study demonstrates how integrating Islamic environmental values with sustainable practices transforms mosques into centres of ecological education and local climate action. The Compost Waqf initiative bridges spiritual responsibility with environmental stewardship, providing a scalable and replicable model for mosques to address global climate challenges while fostering collective awareness and behavioural change within communities. The research highlights the strategic role of mosques in promoting ecological resilience, positioning them as key actors in climate change mitigation efforts.